DESAIN DAN PEMBUATAN KURSI AYUNAN UNTUK POS PENDIDIKAN ANAK USIA DINI - Syamsul Hadi; Ach. Muhib Zainuri; Nurhadi Nurhadi; Nurchajat Nurchajat; Purwoko Purwoko (P3M Politeknik Negeri Malang, 2025)
Early childhood education of Melati Bangsa has only static arcades that still restrict the creativity of children in play as a limitation encountered. The purpose of community service is to facilitate children early age (less than 5 years) in order to build a game together in an exciting atmosphere in the swing chairs capacity of 6 children who are facing each other. Teachers or parents/guardians have responsibility of overseeing and swinging the swing chairs that can be accompanied by the providing of learning through the accompaniment of an interesting story, so learning can be more effective and achieve goals. Methods of community service include: survey with teachers and principal, the availability of areas for installation of swing chairs, design of swing chairs in accordance with the size of the students also anticipate the possiblility that must be strong if it is used by 4 adults, manufacturing swing chairs, painted steel construction and wood, mounting frame and chairs, foundation construction, and testing the chairs and installation of a chain lock. Results obtained in swing chair that can be used by 6 students and 1 teacher simultaneously while receiving lessons from teacher.